Corporate Social Responsibility, Brand Trust, and Technological Innovation as Drivers of Corporate Sustainability Performance: A Bibliometric Analysis - Lirameira Latifah (Universitas Negeri Surabaya, 2025)
During the last few decades, companies’ policies on Corporate Social Responsibility (CSR), brand trust, and technological advancement have grown to be significant determinants of sustainability performance for organizations in all sectors. This study conducts a bibliometric analysis in order to look into how CSR, trust in the brand and technological advancement act in a chain towards improving sustainable business operations. Merging and structuring existing literature, we outline certain mechanisms that companies have in order to improve their sustainable performance, including key areas of disadvantage and limitations of these practices. The dissolution of the analysis emphasizes that active CSR practice and brand trust induce customers’ preference while technological change makes the processes of resource exploitation more advanced and environmentally friendly. The study suggests useful strategies for both researchers and practitioners that focus on the outcome of corporate sustainability from the nexus of social responsibility, trust accompanied with innovation.